Relationship between family functions with depression in palliative patients - Johan Kurniawan; Ni Ketut Putri Aryani; Ida Ayu Kusuma Wardani (Journal of Clinical and Cultural Psychiatry, 2021)
Background: Diseases or health problems are a part of life that can occur at any time. Terminal disease represents a patient's irreversible health condition, so that this group of patients can be given a therapeutic approach known as palliative care. Patients who experience significant conflict in the family can increase the likelihood of depression. Patients and Methods: This is a descriptive cross-sectional study in 32 subjects chosen by consecutive sampling. Measuring instrument used was Beck’s Depression Inventory. The family function scale is derived from the McCaster’s Model of Family Functioning known as the Family Assessment Device (FAD). Results: In this study, the average age of the sample was 46 years, unmarried from high school education. In the description of family functions obtained with overall results with moderate function. Correlation between the two things was found to be a weak negative correlation between FAD score and BDI score. The smaller the value score of FAD then will the greater the value of BDI. The worse the function of the family will be more severe levels of depression experienced by the sample in this study. Conclusion: We found there was a significant weak negative correlation between family function and depression in palliative patients at Sanglah Hospital Denpasar.